"A comparative study of conventional impressions versus intraoral scanning in prosthodontics" (Al-Farooq Journal of Sciences, 2026)
Background: The transition from conventional to digital workflows is one of the most significant shifts in modern dentistry. This study aimed to evaluate the comparative effectiveness of traditional versus digital impression techniques, focusing on accuracy, patient experience, and workflow efficiency.Objective: This study aims to compare conventional impression techniques with intraoral scanning using modern technologies in terms of accuracy, efficiency, patient comfort, and clinical outcomes in fixed prosthodontics and orthodontics.Methodology: A structured questionnaire and clinical observations were conducted with a sample of 48 practitioners, including general dentists, specialists, and dental technicians with diverse field experience. Data were analyzed to identify trends in clinical adoption, economic feasibility, and technical challenges.Results: The findings reveal a decisive professional consensus (90%) on the superior accuracy of digital methods. Digital impressions significantly reduced patient discomfort (35% of traditional method issues) and streamlined clinic-laboratory communication. Notably, 69% of participants justified the high investment costs of digital equipment through improved clinical outcomes. However, a "digital gap" was identified, as 79% of practitioners do not yet utilize specialized design software, largely due to training deficits and software costs.Conclusion: While digital technologies are fundamentally enhancing the precision and comfort of dental procedures, their full potential remains untapped. The study emphasizes that the future of digitalization in dentistry depends not only on equipment acquisition but also on bridging the skills gap through integrated educational workshops and continuous professional training.
Keywords: digital dentistry, intraoral scanning, Conventional Impressions, Accuracy, Patient Comfort, Libya, western region, dental education